Parameter Optimization of PID Controller Based on PSO for Multi-leaf Collimator - Zhang Xin (Institute of Advanced Engineering and Science, 2013)
According to the control requirements of the leaves’ position precision in the multi-leaf collimator, the structure and working principle of the multi-leaf collimator in the conformal radiation therapy apparatus are described. The motor that drives the leaf of the MLC is taken as the control object. The module of the motor has been established. Then the PSO algorithm is used for the parameter optimization of PID controller that outputs the given expectation to the motor, in order to ensure the position accuracy of the MLC leaves. The experimental results indicate that this algorithm can meet the needs of the control precision of the leaves’ position of the multi-leaf collimator, and each control index is obviously superior to the traditional method for PID control. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.2759